The development of high performance band-stop filter for anti-sway control of a gantry crane system - Nur Izana, Hafiza (2009)
Gantry crane is a load-lifting system consists of three main components which are trolley, bridge and gantry. Gantry can be described as a supporting structure that is rigidly affixed to hold the trolley’s movement on and parallel to a bridge. However, due to the heavy and bulky size also swaying of the payload during the movement, gantry crane are difficult to control in such a way that the load reaching the desired destination in minimum time. So, the main purpose of controlling a gantry crane is transporting the load as fast as possible without causing any excessive sway at the final destination by using a two-dimensional gantry crane model and feed forward approach. The applications and performance of Band - stop filter is the technique used in this project to actively control the sway angle of the rope of gantry crane system. The dynamic behaviors are analyzed using CEMTool, SIMTool and MATLAB. An unshaped bang – bang torque input is used to determine the characteristic parameters of the system for the design and evaluation of the Band – stop filter techniques. Project results of the response of gantry crane to the input are presented in time and frequency domains. The effects of the order of the filtered Band – stop filter on the performance of the system are investigated. Finally, a comparative assessment of the amplitude polarities of the system performance is presented and discussed.